Membentuk Karakter Pemuda melalui Pencak Silat Sekinci-Kinci - Suranti, Bibit; Karsiwan, Karsiwan (Aceh Anthropological Journal, 2024)
The increasing tide of globalization penetrating Indonesia is having an impact on the erosion of the moral character of Indonesian youth. Globalization causes between nations in the world to no longer have a boundary wall, so that information, culture, and negative impacts from other countries easily enter Indonesia. The character of Indonesian youth, which should be based on Pancasila and the Constitution as the identity of the nation, has been replaced by characters that should not be such as hedonism, capitalism and individualism. Pencak silat is a typical Indonesian culture that can be used as a means of building the character of the nation's youth. Pencak Silat training, incorporating both spiritual and physical elements, aims to cultivate individuals with civility and good character. Qualitative research is applied to this research by utilizing a number of data sources from interviews, documentation, internet content, literature reviews, and observations. The results of this study can be concluded if the character of the youth can be formed through the practice of pencak silat sekinci-kinci based on art, martial arts, sports, brotherhood, and spiritual. Meanwhile, the characters that can be formed in young people are such as, love of the country, love of local culture, simple, confident, polite and polite. Harmonization of the concept of youth character building with the aim of pencak silat sekinci-kinci, namely; Maintaining kinship, solidarity, mutual love and nurturing within the framework of the unity of the Indonesian nation based on the teachings of Islam, Pancasila and the 1945 Constitution.Abstrak: Arus globalisasi yang semakin meningkat berdampak pada terkikisnya karakter moral yang dimiliki para pemuda Indonesia. Globalisasi menyebabkan antar bangsa di dunia tidak lagi memiliki dinding pembatas, sehingga informasi, budaya, serta dampak negatif dari negara lain mudah masuk ke Indonesia. Karakter pemuda Indonesia yang seharusnya berdasarkan Pancasila dan UUD sebagai identitas jati diri bangsa telah beralih dengan karakter yang tidak seharusnya seperti hedonisme, individualis, dan kapitalisme. Pencak silat ialah kebudayaan khas Indonesia yang dapat dijadikan sebagai sarana pembentukan karakter pemuda bangsa. Unsur rohani serta jasmani yang terkandung pada latihan pencak silat diharapkan dapat melahirkan individu yang beradab dan berkarakter baik. Penelitian kualitatif diterapkan pada penelitian ini dengan memanfaatkan sejumlah sumber data dari hasil wawancara, dokumentasi, konten internet, tinjauan pustaka, serta observasi. Hasil dari penelitian ini dapat disimpulkan jika karakter para pemuda bisa dibentuk melalui latihan Pencak Silat Sekinci-kinci berdasarkan pada kesenian, bela diri, olahraga, persaudaraan, serta spiritual. Sementara karakter yang dapat terbentuk di dalam diri pemuda yakni seperti, cinta tanah air, cinta kebudayaan lokal, sederhana, percaya diri, sopan dan santun. Harmonisasi konsep pembentukan karakter pemuda dengan tujuan Pencak Silat Sekinci-kinci yakni; menjaga kekeluargaan, kesetiakawanan, saling asah asih dan asuh dalam kerangka persatuan bangsa indonesia berdasarkan ajaran islam, pancasila dan UUD 1945.